Bismuth-based coating layer for sliding member
By adjusting the grain orientation distribution and adding particle dispersion in the bismuth-based cover layer, the problem of insufficient fatigue resistance of the bismuth-based cover layer in high-output engine bearings is solved, and higher fatigue resistance and stability are achieved.
Patent Information
- Application Number
- CN202480004760.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-05-31
- Filing Date
- 2024-05-15
- Publication Date
- 2025-06-20
AI Technical Summary
The bismuth-based cover layer has the problem of insufficient fatigue resistance in applications such as high output engine bearings, especially because the addition of hard particles and solid lubricating particles affects the fatigue performance of the cover layer.
By adjusting the orientation distribution of grains in the matrix of the bismuth-based cover layer, ensure that the grain ratio of Grain Orientation Spread (GOS) is less than 1 degree to reach more than 85%, and particles are dispersed and added in the matrix to improve the fatigue resistance of the cover layer.
While maintaining the wear resistance and low friction properties of the cover layer, the fatigue resistance of the bismuth-based cover layer is significantly improved, and fatigue caused by cracks is reduced, thereby extending the service life of the sliding member.
Smart Images

Figure CN120187898A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an improvement of a bismuth-based coating for a sliding member, a method for manufacturing the same, and a sliding member provided with the coating. Background Art
[0002] From the viewpoint of reducing the environmental load and the like, bismuth is used as a matrix of a coating for a sliding member. Hard particles and solid lubricant particles may be contained in the bismuth-based coating. Thereby, the coating obtains abrasion resistance and low friction (Patent Documents 1 and 2).
[0003] In addition, as prior art documents related to the present invention, refer to Patent Document 3.
[0004] Prior Art Documents
[0005] Patent Documents
[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 2003-156046
[0007] Patent Document 2: Japanese Patent No. 6905926
[0008] Patent Document 3: British Patent Publication No. 2534120 Summary of the Invention
[0009] Problems to be Solved by the Invention
[0010] When a sliding member is used as a bearing of a recent high-output engine, it has been found that the bismuth-based coating containing hard particles and solid lubricant particles has the following problems.
[0011] That is, since the matrix is bismuth-based, the brittleness due to the properties of bismuth affects the coating, and the coating is prone to fatigue.
[0012] It is considered that the fatigue resistance of the bismuth-based coating containing hard particles and solid lubricant particles is generally worse than that of the bismuth-based coating not containing these particles.
[0013] Additive particles such as hard particles and solid lubricant particles impart abrasion resistance and low friction to the bismuth-based coating. Therefore, when the bismuth-based coating is applied to a sliding member such as a bearing of a high-output engine, it is required to contain the additive particles therein.
[0014] Means for Solving the Problems
[0015] The present inventors have conducted intensive studies to solve the above problems, focused on the orientation difference of the crystal grains constituting the matrix of the bismuth-based coating, and conceived the following invention. That is, the first aspect of the present invention is defined as follows.
[0016] A bismuth-based coating, which is a bismuth-based coating for a sliding member, includes: a polycrystalline matrix including grains made of a material containing bismuth or a bismuth alloy; and additive particles dispersed in the matrix; the matrix includes a region where the grains with a Grain Orientation Spread (GOS) of 1 degree or less account for 85% or more of all the grains.
[0017] Regarding the bismuth-based coating according to the first aspect defined as such, while maintaining the properties (such as abrasion resistance and low friction) imparted to the coating by the additive particles, its fatigue resistance is improved.
[0018] It is considered that the reason is that since the grains with a GOS of 1 degree or less are not likely to be the starting points of cracks, by adjusting their ratio to 85% or more, fatigue caused by cracks is not likely to occur in the matrix.
[0019] Here, the ratio of the grains refers to the number ratio of the grains.
[0020] The layer thickness of the coating is not particularly limited and should be appropriately selected according to the use of the sliding member, etc.
[0021] The bismuth alloy refers to an alloy with bismuth (Bi) as the main component and one or more selected from lead (Pb), indium (In), tin (Sn), antimony (Sb), etc., or an alloy with these elements.
[0022] The average grain diameter of the grains constituting the matrix can be set to 0.1 μm to 5.0 μm. The measurement method of this average grain diameter is: for the cross-section of the coating sample, using any grain observation method, and then measuring the "maximum Feret diameter" (the longest distance between any two points on the contour of the particle) through image analysis software and calculating the average value.
[0023] GOS refers to the average value of the orientation difference between a certain measurement point in the grain and all the remaining measurement points. More specifically, refer to "Analysis of Orientation Difference in Plastic Deformation of Stainless Steel Based on EBSD Method and X-ray Diffraction Method" by Kimura et al., Transactions of the Japan Society of Mechanical Engineers (Series A), Vol. 71, No. 712 (December 2005). And the content of this paper is cited and referred to in this specification.
[0024] The hard particles as the additive particles enhance the mechanical properties of the bismuth-based coating.
[0025] As additive particles for enhancing the abrasion resistance of the bismuth-based coating, particles harder than bismuth or bismuth alloy are used. As the above-mentioned hard particles, one or more selected from carbon fiber, glass fiber, boron nitride, alumina, silicon carbide, silicon oxide, aluminum nitride, and titanium oxide can be used. The average particle size of the hard particles can be 1 nm to 10 μm. More preferably, it is 0.1 μm to 3.0 μm. The average particle size of the above-mentioned hard particles can be measured by laser diffraction / scattering method before being put into the plating solution.
[0026] As additive particles for enhancing the low friction property of the bismuth-based coating, solid lubricant particles are used. As the above-mentioned solid lubricant particles, one or more selected from molybdenum disulfide, graphite, tungsten disulfide, and plate-like grains of boron nitride can be used.
[0027] The average particle size of the solid lubricant particles can be set to 1 nm to 5.0 μm. More preferably, it is 0.1 μm to 3.0 μm. Compared with the shape of the solid lubricant particles being plate-like, it is easier to control GOS when their shape is granular. The average particle size of the above-mentioned solid lubricant particles can be measured by laser diffraction / scattering method before being put into the plating solution.
[0028] The additive particles are not limited to hard particles and solid lubricant particles. In order to improve coating functions such as adhesiveness, corrosion resistance, lipophilicity, and oleophobicity, other arbitrary additive particles can be contained in any blending amount.
[0029] The content of the additive particles in the matrix can be set to 1.0 vol% to 15.0 vol% (second aspect). By making the content of the additive particles within this range, the characteristics from the additive particles can be well manifested in the bismuth-based coating.
[0030] When using a matrix with GOS of 1 degree or less and grains containing bismuth or bismuth alloy being 85% or more, compared with the bismuth-based coating without additive particles, the bismuth-based coating containing additive particles within the above range can further increase the proportion of grains with GOS of 1 degree or less.
[0031] The hardness of the bismuth-based coating is preferably set to 20 HV or more (third aspect). The coating with the above hardness has excellent abrasion resistance.
[0032] The hardness of the bismuth-based coating can be adjusted by changing the content of the hard particles. As described above, in order to control the proportion of grains with GOS of 1 degree or less, the amount of the hard particles is preferably selected from 1.0 vol% to 15.0 vol%.
[0033] The manufacturing method of the sliding member provided with the bismuth-based coating can be specified as follows.
[0034] A manufacturing method of a sliding member includes the following steps: a step of treating the surface of added particles to control the wettability of the surface; a step of putting the treated added particles into a plating solution for bismuth or a bismuth alloy and stirring; a step of preparing a substrate of the sliding member; and a lamination step of laminating a bismuth-based covering layer on the surface of the substrate of the sliding member by using the plating solution into which the added particles are put.
[0035] In the above, in order to control the wettability of the surface of the added particles, any treatment method such as plasma treatment or UV irradiation treatment of the surface can be selected.
[0036] By controlling and increasing the wettability of the surface of the added particles, aggregation of the added particles with each other in the plating solution is prevented. Thereby, the dispersibility of the added particles is improved.
[0037] The amount of the added particles in the plating solution is preferably 15 g to 150 g per 1 L of the plating solution. More preferably, it is 40 g / L to 120 g / L. Thereby, it is possible to easily achieve that the grains having a GOS of 1 degree or less in bismuth or a bismuth alloy, which are the matrix constituting the bismuth-based covering layer, account for 85% or more of all the grains. Although sufficient stirring of the plating solution is required, the stirring conditions do not need to be strictly controlled. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 It is a schematic view showing a sliding member according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE EMBODIMENTS
[0039] Hereinafter, embodiments of the present invention will be described.
[0040] As Figure 1 shown, the sliding member 1 according to the embodiment of the present invention has a structure in which a bearing alloy layer 3 and a bismuth-based covering layer 5 are sequentially laminated on a metal backing layer 2.
[0041] The metal backing layer 2 applied to the sliding member 1 is made of general steel, and the bearing alloy layer 3 uses a soft metal material such as copper or a copper alloy. Sometimes an intermediate layer made of silver (Ag), nickel (Ni), etc. is formed on the bearing alloy layer.
[0042] The above-mentioned sliding member 1 can be arbitrarily designed in shape according to the diameter and movement of the object to be slid (the member to be slid).
[0043] The matrix 5a of the bismuth-based covering layer 5 is a polycrystal composed of bismuth or a bismuth alloy. In addition, added particles 5b are uniformly dispersed in the matrix 5a.
[0044] The bismuth-based covering layer 5 can be produced by known methods such as electroplating, vacuum sputtering, thermal spraying, and cold spraying.
[0045] In this example, an electroplating method is used to fabricate a bismuth-based coating layer.
[0046] First, a plating solution for bismuth is prepared in advance. The plating solution is not particularly limited, and considering the compatibility with the added particles, a plating solution capable of performing composite plating should be appropriately selected. The sulfonic acid bath is used in this case.
[0047] In addition, the added particles are subjected to UV treatment to make their surfaces easily wettable in the plating solution. It should be noted that the UV treatment device is developed by ASUMI Technology Co., Ltd. (UV surface cleaning and modification device, model: ASM1101N). The conditions are controlled with an illuminance of 0.1 mW / cm 2 ~30 mW / cm 2 using a total output irradiator of 5 W to 250 W, a treatment time of 5 minutes to 48 hours, and a wavelength selected in the range of 185 nm to 365 nm.
[0048] The addition amount of the added particles is 15 g / L to 150 g / L with respect to the plating solution, preferably 40 g / L to 120 g / L.
[0049] The plating solution added with the added particles is sufficiently stirred to prevent the added particles from aggregating. The stirring conditions are not particularly limited. It is preferably to use ultrasonic stirring and mechanical stirring in combination for 0.2 hours to 2.0 hours, preferably 1.0 hour. The ultrasonic stirrer uses QS12 manufactured by Ultrawave Ltd., and the stirring conditions are an ultrasonic frequency of 32 kHz to 38 kHz and an ultrasonic output of 200 W. On the other hand, the mechanical stirrer uses MICROSTAR 7.5 control manufactured by IKA England Ltd., and stirs under the conditions of 110 rpm to 2000 rpm, preferably 600 rpm to 1000 rpm.
[0050] The bismuth-based coating layer 5 is formed as follows.
[0051] The surface of the bearing alloy layer 3 is cleaned and degreased by a general method.
[0052] The surface of the bearing alloy layer 3 is brought into contact with the plating solution added with the added particles and sufficiently stirred, and electroplating is performed under the conditions of a current density of 1 A / dm 2 ~6 A / dm 2 and a plating bath temperature of 20°C to 50°C.
[0053] Those skilled in the art should understand that these plating conditions are not fixed and should be appropriately selected according to the experience of the plating operator.
[0054] The thickness of the bismuth-based coating layer 5 is set to 15 μm. The thickness is not limited to this, but from the viewpoint of fatigue resistance, it is preferably set to a maximum of 30 μm.
[0055] The properties of the bismuth-based coating layer 5 of the examples and comparative examples are shown in Tables 1 and 2.
[0056] [Table 1]
[0057]
[0058] In the above, the cumulative light quantity is the product of the illuminance (mW / cm 2 ) and time (seconds).
[0059] [Table 2]
[0060]
[0061] From the results of Example 3 and Comparative Example 1 in Table 1, it can be seen that if the proportion of grains with a GOS of 1 degree or less is 85% or more of all the grains, the fatigue area will become smaller and the fatigue resistance will be improved. It is further preferably set to 90% or more (refer to Example 2 and Example 3).
[0062] As shown in Table 2, according to the results of Examples 6 to 11 in which the added particles were SiC and the content (vol%) was changed, when the content of the added particles was in the range of 0.5 vol% to 20.3 vol%, the proportion of grains with a GOS of 1 degree or less could be 85% or more of all the grains.
[0063] If the content of SiC as the hard particles increases, the proportion of those with a GOS of 1 degree or less has a tendency to increase, and if it exceeds the specified amount, there is a tendency to decrease. On the other hand, in terms of abrasion resistance, a content of 1.0 vol% or more is more excellent.
[0064] In summary, according to the research of the present inventors, the content of the added particles is preferably set to 1.0 vol% to 15.0 vol%.
[0065] In the above, GOS is obtained in the following manner.
[0066] Specimens of the examples and comparative examples before the fatigue test were prepared in the following manner.
[0067] Cutting was performed in the desired area (assumed to be the part with the highest load in the examples and comparative examples), and mechanical polishing was performed on the cut surface of the specimen embedded in resin. The mechanical polishing process includes sandpaper polishing, polishing (diamond slurry), and fine polishing (colloidal silica). A conductive coating (carbon, gold, etc.) was applied to the polished surface, and then ion milling was performed.
[0068] EBSD device: The product name (registered trademark) equipped with a Symmetry-2 EBSD detector is FEI Versa 3D DualBeam SEM.
[0069] Measurement conditions: Scanning area: 100 μm × 22.9 μm, step size: 30 nm, collection speed: approximately 2000 cps, magnification: 4000 times, grain definition: misorientation of 10 degrees or more.
[0070] In the above, the step size is set to ensure 10 or more measurement points within the smallest grain size. The scanning pattern can be either a quadrilateral grid or a hexagonal grid and can be arbitrarily determined according to the crystal structure.
[0071] To improve the measurement accuracy, the measurement area (scanning area) can be arbitrarily set to include grains in more than 1000 coatings.
[0072] The EBSD images obtained in this way are processed using data analysis software to obtain the GOS of all grains included in the scanning area, and the proportion of grains with a GOS of 1 degree or less included therein is calculated. When obvious noise is confirmed, noise removal processing is performed (the Auto Clean-up function of Oxford's EBSD data analysis software AZtecCrystal is used in the examples and comparative examples).
[0073] It should be noted that according to the research of the present inventors, in the bismuth-based coating manufactured by electroplating, in all the observed areas, the proportion of grains with a GOS of 1 degree or less is approximately the same value.
[0074] The conditions of the fatigue test are as described below.
[0075] Bearing size: Φ56 × L14.2 × t1.5 (mm).
[0076] Oil clearance: 0.060 (mm).
[0077] Rotational speed: 3600 (rpm).
[0078] Load: 100 (MPa).
[0079] Frequency: 60 (Hz).
[0080] Lubricating oil: VG68.
[0081] Oil supply temperature: 110 (°C).
[0082] Shaft material: S55C quenched.
[0083] Shaft roughness: Ra0.05 ± 0.01 (μm).
[0084] Test time: 20 (hours).
[0085] Method of applying load: Starting from 0 load, the load is increased every 15 minutes, and a load of 100 MPa is continuously applied for 20 hours starting from one and a half hours later.
[0086] After repeatedly applying load to the cylindrical sliding member (bearing) in which the rotating shaft is embedded from the radial direction, the surface of the coating layer of the sliding member as the specimen is observed. In this surface, the cracked part becomes the fatigue part. The image obtained by photographing the coating surface of the sliding member with a microscope (VHX-8000 manufactured by KEYENCE Corporation) is processed by the supporting software, and the area ratio of the cracked part to the entire surface is calculated. The obtained area ratio is recorded as the fatigue area ratio in Table 1 and Table 2. When the fatigue area rate is 20% or less, it is considered to have fatigue resistance.
[0087] The amount (vol%) of the added particles in the coating (bismuth-based coating layer) is the area rate obtained by cross-sectional observation (the area ratio of the added particles to the entire coating layer).
[0088] The measurement of the hardness HV is carried out according to the cross-sectional specimen by a micro-Vickers hardness tester (HM-220 manufactured by Mitutoyo).
[0089] The wear amount is obtained in the following manner. In the coating layer before and after the test, the thickness at a position 1 mm away from the end is measured respectively by a thickness gauge (manufactured by our company), and the thickness change amount (wear amount) after the test is obtained. The results in Table 2 are the average values of two positions 1 mm away from the left end and 1 mm away from the right end.
[0090] The present invention is not limited by any of the descriptions of the above embodiments of the invention. Various deformation schemes within the scope that can be easily conceived by those skilled in the art without departing from the description of the claims are also included in the present invention.
[0091] Description of reference numerals
[0092] 1: Sliding member;
[0093] 2: Metal backing layer;
[0094] 3: Bearing alloy layer;
[0095] 5: Bismuth-based coating layer.
Claims
1. A bismuth-based coating, which is a bismuth-based coating for a sliding member, The invention comprises: a polycrystalline matrix comprising grains composed of a material containing bismuth or a bismuth alloy; and additive particles dispersed in the matrix; The matrix includes a region in which the grains having a GOS, that is, a grain orientation distribution of 1 degree or less account for more than 85% of all the grains.
2. The bismuth-based covering layer according to claim 1, wherein The content of the added particles in the matrix is 1.0 vol% to 15.0 vol%.
3. The bismuth-based covering layer according to claim 1, wherein The bismuth-based covering layer has a hardness of 20 HV or more. 4 . A sliding member comprising the bismuth-based coating layer according to claim 1 .
5. A method for manufacturing a sliding member, comprising the following steps: a step of treating the surface of the added particles to control the wettability of the surface; The step of adding the treated added particles into a plating solution for bismuth or bismuth alloy and stirring the solution; a step of preparing a base body of a sliding member; as well as The lamination step is to laminate a bismuth-based coating layer on the surface of the base of the sliding member using a plating solution into which the additive particles are added.
6. The manufacturing method according to claim 5, wherein: The amount of the added particles added to the plating solution is 15 g to 150 g per 1 L of the plating solution.
7. The manufacturing method according to claim 5, wherein: The surfaces of the added particles are subjected to plasma treatment and UV irradiation treatment to improve the wettability of the surfaces in the plating solution.
Citation Information
Patent Citations
Bismuth-based composite coating for overlay applications in plain bearings
GB2534120A
Sliding member
JP2003156046A